Differences in the ecology and behaviour of reindeer populations in the USSR - Baskin, Leonid M. (Rangifer, 1986)
The population differences in ecology and behaviour of reindeer (Rangifer tarandus spp.) is closely paralleled by the characteristic features of reindeer husbandry which reveals the close relationship between behaviour and husbandry. The western portion of the reindeer husbandry region in the USSR is vast. The reindeer are maintained on a semi-loose basis; the herd is scattered over the range; the social activity of the reindeer is lower; the herdsmen gather the herd using dogs, the herdsmen migr.ate together with the herd during the summer, grazing the herd in the vicinity of the tent for 2-5 days at a time. In the eastern portion of the region (Yakutia, Chukotka, Kamchatka), the ranges are more restrictive; the reindeer are grazed in a compact mass in summer; their feeding and movement are rigidly regulated; their social activity is high; the herd is gathered in foot without dogs. In summer, herdsmen follow the herd with light tents, the place of grazing being changed almost daily. In the taiga reindeer are raised mostly for transportation, although the hides and meat are also important; the reindeer are bigger, tamer and can be used for riding. The herds are small and the management of them is aimed at retaining the reindeer near home or the camp; migrations are short; often forest reindeer husbandry is of a sedentary nature. Attempts to change the pattern of reindeer husbandry and the methods of herding are not always successful. The harmony of environmental conditons, morphology, physiology, ecology and behaviour of reindeer and methods of husbandry are more easily disrupted than altered.